Numerical solution of singular Lur'e equations. Issue 1 (December 2014) - Reis, Timo; Rendel, Olaf
Abstract We consider a generalization of Lur'e equations for differential‐algebraic systems. We aim to numerically solve these equations. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)